PENENTUAN DENSITAS PLASMA HIDROGEN NONTERMAL PADA TEKANAN RENDAH - Nelda Ipkawati; Saktioto Saktioto (Universitas Riau, 2019)
Before producing hydrogen plasma low pressure in experiment, it is necessary to know the density equilibrium process through a simulation. Hydrogen species densities of non-thermal plasma at low pressure is simulated using chemical kinetik model by Runge Kutta method. This simulation carried out to determine the equilibrium process of densities and reaction rates of hydrogen species in achieving equilibrium conditions. The equation used time-dependent continuity equation and Arrhenius form. The hydrogen species consist of electrons, H, H2, H+ and H2+. The results of show that electron density, H, H2, H+ and H2+ are respectively 1020,23m-3, 1019,69m-3, 1019,91m-3, 1019,39m-3 and 1018,43m-3 during of 23-24 ns. These describe that the density of each species of hydrogen very fast to achieve equilibrium conditions, while the value of the reaction rate obtained can be concluded that the value of the largest reaction rate is the impact ionization process with a value of 9.86x1052m-3 s-1and the smallest one is dissociation process with a value of 1.22x10-5m-3 s-1.